Conductive magnetic sol–gel films. Issue 41 (28th September 2015) - Vinogradov, Vladimir V.; Felner, Israel; Nowik, Israel; Avnir, David
Abstract : We report the development of new conductive–magnetic composite films obtained by the entrapment of silver nanowires (AgNWs) in sol–gel derived magnetite. Abstract : We report the development of new conductive–magnetic composite films obtained by the entrapment of silver nanowires (AgNWs) in sol–gel derived magnetite. The resulting films are highly adhesive on PET, highly flexible, and translucent. The films were subjected to characterization including resistance, magnetic response, Mössbauer measurements, heat dissipation, and critical bending angle analysis. The addition of a small amount of alumina nanoparticles significantly increases the composite's density and adhesion to the substrate. Capillary pressure arising from the evaporation of the solvent during film formation is the driving force for the high homogeneity of the composite films and for the percolation of the AgNW.